A Parent- Implemented Phono Graphix ™ to Improve the Phonological Awareness of the Children at Risk- of Reading Difficulty - Antonio, Mahlen; Ayuyao, Nunilon (ETERNAL (English, Teaching, Learning and Research Journal), 2023)
This study was conducted during COVID 19 pandemic when face-to-face instruction was suspended and access to teacher-led reading intervention was unavailable. Different distance learning modalities were implemented so as not to disrupt the continuity of the basic education. The challenge with these modalities was not only in dealing with students who were not capable of learning by themselves but moreso in managing students who were already struggling in reading even during face-to-face instruction. In the old normal, it is resolved by having struggling readers undergo remediation or intervention with the supervision of either teachers or tutors; however, such resolution is impossible with the present situation. One of the possible solutions was to solicit the help of the primary school partners- the parents. Using quasi-experimental method with pre-test and posttest comparison, the efficacy of a parent-implemented Phono-Graphix™ program in improving the phonological awareness (PA) skills of children at-risk of reading difficulty was examined. Parents of 11 grade 1 children implemented the reading intervention five times a week for 20-30 minutes per session. PA skills of the participants were assessed prior and after the reading program. Descriptive analysis was used to statistically describe the pre-test and posttest results as well as graphs for visual presentation. To test the difference in scores, Wilcoxon signed-ranks test was utilized where a p-value less than 0.05 was considered significant. Findings revealed that phonological awareness skills of the participants improved after eight weeks of parent-implemented Phono-Graphix™ program. Results and implications for future research are further discussed.